Compact beam-steerable lens antenna for 60-GHz wireless communications - Costa, Jorge R. (2014)
This paper presents a new concept of steerable beam antenna composed by a dielectric lens which pivots in front of a single stationary moderate gain feed. The lens not only allows steering mechanically the beam in elevation and full azimuth, but further increases the gain up to 21 dBi. The solution is broadband, including the entire international unlicensed spectrum from 57 GHz to 66 GHz. A fabricated prototype shows the possibility of tilting the beam from - 45deg to + 45deg for all azimuths with gain scan loss below 1.1 dB and radiation efficiency above 95%. The arrangement is very simple, it does not require rotary joints, it is low cost and compact, lens plus feed volume being of the order of 3 times 3 times 3 cm3 with lens weight less than 10 g.